Ответы и объяснения

2014-03-17T06:29:22+00:00
A^4 * a^(-6)=a^(-2)=1/9 ^(-2)=9/1² = 81

4x+3/4 - 2x+2/4 = 4/4
4x+3-2x-2=4
2x=3
x=1.5
2014-03-17T06:34:30+00:00
3)1                                                                                                                                  4х+3-2х+2 ровно 1                                                                                                           4х+2х ровно 1-3-2                                                                                                              2х роано -4                                                                                                                    х ровно -2